Examining the relationship between war and interest-based transactions: the case of the Ottoman empire - Mubasshera, Hamida; Kassim, Salina (Emerald Group Publishing, 2015)
This paper attempts to provide a deeper understanding of the verseswhere Allah has declared war against people who deal with interest by examining the relationship between war and interest based transaction.It systematically and choronologically explores the major economics events of the late Ottoman era that contributed in shaping the fate of the empire.Then it proposes that the significance of the abovementioned metaphor is not limited only to spiritual dimension, rather can also be extended to literal perspective.